2021
DOI: 10.1177/23259671211026247
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Third and Fourth Digits and the Second and Fifth Digits of the Flexor Digitorum Superficialis Muscle to Elbow Valgus Stability

Abstract: Background: Thiel cadavers have been reported to have lifelike flexibility and mechanical properties, but whether they are useful for measurement of the ulnohumeral joint space (JS) is unclear. The contributions of the third and fourth digits and the second and fifth digits of the flexor digitorum superficialis (FDS) to elbow valgus stability are also unknown. Purpose: To (1) clarify whether Thiel cadavers can be used for JS measurement on ultrasound and (2) identify the contributions to valgus stability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“… 25 , 29 Recently, studies have reported that increasing FDS function increases the medial-side stability in valgus stress and helps to improve baseball players with ulnar collateral ligament injury. 9 , 18 , 22 , 24 Regarding finger movements during pitching motion, the force of the thumb and ring fingers is greatest just before the maximum shoulder external rotation, whereas the force produced from the index and middle fingers reaches the peak just before the maximum shoulder external rotation and ball release. 11 Previous studies using cadavers have reported that the index, small, and independent small fingers adhere to the anterior oblique ligament of the MCL.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 29 Recently, studies have reported that increasing FDS function increases the medial-side stability in valgus stress and helps to improve baseball players with ulnar collateral ligament injury. 9 , 18 , 22 , 24 Regarding finger movements during pitching motion, the force of the thumb and ring fingers is greatest just before the maximum shoulder external rotation, whereas the force produced from the index and middle fingers reaches the peak just before the maximum shoulder external rotation and ball release. 11 Previous studies using cadavers have reported that the index, small, and independent small fingers adhere to the anterior oblique ligament of the MCL.…”
Section: Discussionmentioning
confidence: 99%
“…The CV% was calculated for each athlete and then averaged out across the team through the division of the standard deviation by the mean of COD (CV = 100 (SD/M)). The minimum detectable difference at the 95% CI (MDD) was calculated using the following equation: MDD = z × standard error of measurement × √2, where z is 1.96 and the standard error of measurement is SD√(1−ICC) [ 47 , 48 , 49 ]. Effect size was presented using partial eta squared (η p 2 ), were 0.01 < η p 2 < 0.06 is defined as a small effect, 0.06 < η p 2 < 0.014 is defined as medium, and η p 2 > 0.14 resembled a large effect [ 50 ].…”
Section: Methodsmentioning
confidence: 99%